Klasyfikacja obiektów symbolicznych oparta na kryteriach - Pełka, Marcin (Symbolic Criterion-Based Divisive Clustering, 2006)
The article presents symbolic criterion-based divisive clustering proposed by Diday. The aim of the article is to present all the parts of this method and to characterize it. The article presents also suggestions of Polish translations for words used by Diday. The usage possibility was presented on the basis of car marked clustering. At the end of the article some weaknesses and advantages of this idea were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (16); 2006; nr 1100, s. 75-85